Kepuasan Pelanggan di Kedai Torang Galaxy Bekasi - Hazmi, Hamad; Hidayat, Arif; Ekawati, Rina (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to understand how factors can affect customer satisfaction and find out what factors can affect customer satisfaction at Kedai Torang. The method used in this research is mixed method. With the research subject being customers at Kedai Torang. Data collection is obtained through questionnaires for customers and in-depth interviews with the owner of Kedai Torang. Data obtained from literature studies and documentation from photographs taken by the author. The results of research from tangible indicators (concrete) the average value of customers agrees in the aspect of facilities to employees, reliability (hope) the average value of customers agrees in the aspect of timeliness and friendliness of employees, responsiveness (responsiveness) the average value of customers agrees in the aspect of responsive service, assurance (guarantee). The conclusion of the study is about certain aspects that affect customer satisfaction. which consists of tangible, reliability, responsiveness, assurance, and empathy, has provided deep insight into how customers assess various aspects of service. The average score obtained from each indicator indicates that most respondents are satisfied with the service and quality provided by Kedai Torang.